Research Study on Impact Assessment of Accelerated Irrigarion Benefit Programme Final Report Phase-II - Planning Commission (Planning Commission, 2002)
Research study on impact assessment of Accelerated Irrigation Benefit Programme (AIBP, in operation since 1996-97) has been entrusted to WAPCOS (India) Ltd., by Planning Commission, Govt, of India in March 2001. The study involves 20 major/ medium/ ERM projects in 19 States & 26 minor irrigation projects in 4 North- Eastern States. The study has been carried out in two phases (Phase - I & Phase - II) based on secondary data/ information available with the client, their agencies and the project authorities as per terms of reference (TOR). The projects for study have been selected in consultation with CWC / State Govts.
Water and Power Consultancy Services (India) Ltd. International Consultants in Water & Power Development (A Government of India Undertaking)
Government of India Planning Commission
Keywords: Studies entrusted to WAPCOS; Background of AIBP; Guidelines issued by MOWR; Eligibility criteria for CLA under AIBP; Mode of funding; Details of CLA released & expenditure; Projects identified for impact assessment; Major; medium and ERM projects